State-of-the-art and future directions for green human resource management: Introduction to the special issue - Susan E. Jackson; Douglas W. S. Renwick; Charbel J. C. Jabbour; Michael Müller-Camen (Zeitschrift für Personalforschung (ZfP), 2011)
The topic of environmental sustainability is generating increased concern among business executives, governments, consumers, and management scholars. As these stakeholders struggle with the challenges and opportunities presented by an array of environmental issues, HRM scholars and practitioners alike have been relatively slow to engage in the ongoing discussions and debates. Through this special issue on Green HRM, we seek to stimulate the field of HRM to expand its role in the pursuit of environmentally sustainable business. In this introduction to the special issue, we first provide an overview of the articles that appear in the special issue. Next we present a detailed discussion of research questions that arise from a consideration of several functional HRM practices, including performance management; training, development, and learning; compensation and rewards; and organizational culture. We conclude by describing opportunities for research at the intersection of strategic HRM and environmental management. If pursued with vigor, research addressing this extensive agenda could begin to establish a healthy field of Green HRM scholarship. – – Nachhaltigkeit in Umweltfragen ist ein immer wichtigeres Anliegen für Unternehmensleitungen, Regierungen, Konsumenten und Wirtschaftswissenschaftler. Während diese Akteure mit den Herausforderungen und Möglichkeiten unterschiedlicher Umweltfragen ringen, engagieren sich Personalwirtschaftler relativ zurückhaltend in entsprechenden Diskursen. Mit diesem Sonderheft zum Umweltorientierten Personalmanagement möchten wir die Personalwirtschaft stimulieren, ihre Rolle zu erweitern und sich mehr mit umweltorientierten Nachhaltigkeitsfragen zu beschäftigen. In der Einleitung stellen wir zuerst die Beiträge dieses Heftes vor und diskutieren dann die Forschungsfragen, die sich aus einer Betrachtung verschiedener Personalfunktionen ergeben. Am Ende beschreiben wir die Möglichkeiten für Forschung an der Schnittstelle von Strategischem Personalmanagement und Umweltweltmanagement. Energisch verfolgt, kann Forschung entlang dieser extensiven Agenda helfen, Umweltorientiertes Personalmanagement zu etablieren.
Keywords: J24; L60; M10; M12; M14; M50; M54; Q01; 330; Green HRM; environmental sustainability; sustainable HRM; environmental management; strategic HRM